3D printed kidney model could be an important educational tool for residents. Issue 2 (18th October 2022) - Yamazaki, Masahiro; Takayama, Tatsuya; Fujita, Akifumi; Kikuchi, Tomohiro; Kamimura, Tomoki; Myoga, Hiroaki; Mayumi, Shozaburo; Yazaki, Kai; Katano, Saki; Komatsubara, Maiko; Kamei, Jun; Sugihara, Toru; et al.
Abstract: Introduction: This study aimed to evaluate whether it is useful for junior physicians to use a three‐dimensional (3D) kidney model when evaluating the R.E.N.A.L. nephrometry score. Materials and Methods: An expert and four urology residents retrospectively evaluated the R.E.N.A.L. nephrometry scores of 64 renal tumors (62 patients) that underwent robot‐assisted partial nephrectomy at our hospital. The expert evaluated 64 R.E.N.A.L. nephrometry scores with computed tomography (CT), whereas four residents evaluated 32 cases using CT alone and the other 32 cases using CT and a 3D kidney model. The consistency between the expert and residents was assessed by Cohen's kappa score. Patient‐specific 3D kidney models were created in a gird style using a 3D printer based on CT or magnetic resonance imaging of the patient. Results: For all four residents, the accuracy of the overall R.E.N.A.L. nephrometry score was significantly higher with the 3D model and CT than with CT alone ( P < .001). Regarding the individual components of the R.E.N.A.L. nephrometry score, the accuracy rates of "E, " "N, " "A, " and "L" scores were higher with the 3D model and CT than with the CT alone ( P = .020–.089). Conclusion: Patient‐specific 3D‐printed kidney models could improve the resident's understanding of the renal tumor complexity and could be an important educational tool for residents.